PENGARUH JUMLAH PENUMPANG DAN JAM KERJA TERHADAP PENDAPATAN TUKANG OJEK DI KECAMATAN JAMBI TIMUR - Sudirman Sudirman; Wiwin Alawiyah (Universitas Batanghari Jambi, 2012)
Motorcycle taxi is one of the areas of employment in the informal sector paratransit mode operating in Indonesia. Paratransit term applies to a small passenger vehicle that operates by pulling unofficial costs, and serve a number of places as an alternative to regular bus transportation service. Paratransit operates in the environment variable - fixed space (Jitney), or space-time variables fixed or variable - time range (taxi rides - including a motorcycle taxi call therein). Motorcycles motorcycle to be one type of transportation service is effective because it can be used any time, the service is quite extensive and relatively low cost. Motorcycle taxi is also a major transport for those living in the suburbs or in rural areas therefore transportation paratransit taxi.In this study, the income of a motorcycle in the district of the city of Jambi east jambi influenced by two variables, number of passengers and number of hours of work. Motorcycles motorcycle to be one type of transportation service is effective because it can be used any time, the service is quite extensive and relatively low cost. Motorcycle taxi is also a major transport for those living in the suburbs or in rural areas therefore transportation paratransit taxi.This study uses primary data analyzed by the method of observation to have data on the influence of the number of passengers and hours worked on a motorcycle revenue, In this study the entire study population is a motorcycle that is in the Eastern District Jambi city of Jambi , that as many as 743 people.The conclusion from this study showed variable X1 (number of passengers) and X2 (hours worked) can explain the changes in a motorcycle revenue by 54% and the number of passengers (X1) and hours worked (X2) is very significant effect on earnings handyman motorcycles with the F value is calculated 57 291 is greater than F-table value of 19.2. If the number of passengers increases a person then the income of Rp taxi ride. 7202.185, and if the hours worked increased 1 hour then a motorcycle revenue will increase by Rp. 2535, 868. Thus, to encourage increased motorcycle taxi driver in District of income East Jambi Jambi City should encourage an increase in the number of passengers with a better service strategy and condition of the vehicle a more vibrant.Keyword : Passengers, Hours of Work, Income